AN ANALYSIS OF MATHEMATICAL UNDERSTANDING ABILITY VIEWED FROM CREATIVE ATTITUDE - Nida Sri Utami (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
The purpose of this research is to analyze mathematical understanding ability, especially students of  mathematics education at second semester. Understanding ability that was researched is about group of algebra structure. This research use descriptif qualitative method. Subject at this research are second semester  mathematics education student in Universitas Muhammadiyah Surakarta in academic year 2018/2019. Data in this research were  obtained with interview, test, and documentation. Results showed student with high creative attitude has translation ability, interpretation ability, and exploration ability. Student with medium creative attitude has translation ability and  interpretation ability, but  hasn’t exploration ability. Student with low creative attitude has translation ability, but hasn’t interpretation ability and exploration ability